Distribution and Impact of Beetles in Agriculture and Integrated Pest Management (IPM) - SHUBHAM; SANJEEVANI; Bali, Gaganpreet (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2025)
The Indian subcontinent, with its diverse landscapes and climate variables, harbors a rich and varied beetle fauna. This effort aims to provide an overview of the distribution patterns of beetles across the region, considering factors such as geographical location, altitude, temperature, and rainfall. By analyzing existing literature and conducting field surveys, we had identified key beetle hotspots and assess the impact of human activities on their distribution. Understanding the distribution of beetles in the Indian subcontinent is crucial for conservation efforts and ecological research. The species which are studied: Blister Beetle, Aquatic Beetle, Ladybird Beetle, Dung Beetle, Ground Beetle. This review article focusses on the major beetles found in the Mohali region of Punjab. This article also focuses on the IPM which is the holistic approach to pest management that combines various strategies to minimize pesticide use while maintaining crop productivity and profitability. Beetles play a significant role in IPM strategies, both as targets of control measures and as beneficial agents that can be harnessed for natural pest suppression.